Consideraciones sobre la responsabilidad administrativa de las personas jurídicas conforme al marco normativo peruano - Sánchez Cateriano, María del Pilar (2018)
Throughout this article I seek to present the recent legal framework regarding Compliance about the —criminal— administrative responsibility of legal entities as a main focus of national policies about the fight against corruption, money laundering and terrorism financing. I will explain the applicable scope of the regulations and the most relevant topics regarding them, including the importance of the implementation of a prevention model by companies as an exculpatory of administrative responsibility.